Awareness of Dental Practitioners Regarding Biocompatibilty of Dental Materials - Uzma Hasan, Muteen Fatima, Humera Khan, Saeeda Zia, Aatika Khan, Maryam Habib (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was done to evaluate awareness of dental practitioners regarding biocompatibility of dental materials among dental practitioners. Study Design: Cross sectional study Place and duration of study: This study was conducted in Islamic international dental college Islamabad during June 2019 to December 2019. Materials and methods: This was a cross sectional questionnaire based study. Questionnaires were distributed to house officers and post graduate trainees (N=100) of Islamic International Dental Hospital. The recorded data was analyzed using SPSS2015 (version 23) software. Results: 85% of dental practitioners had knowledge about biocompatibility of polymer based materials. 89% were aware of type of adverse reactions associated with latex gloves. 64% of dental practitioners had awareness that eugenol is a cytotoxic substance present in zinc oxide eugenol. 7% of dental practitioners knew about the various methods to diagnose titanium allergy. Practical implication: This study will help the dental practitioners to comprehend what type of allergies are prevalent in their local population and which dental material can give best results without adverse effects. Conclusion: Our participants have sufficient knowledge about the biocompatibility of dental materials but the knowledge about titanium allergy needs to be enhanced. Keywords: awareness, biocompatibility, dental practitioners, dental materials